Assessment of mealtime behaviors in Chinese children with autism spectrum disorder - Zhang, Lili; Zhang, Yunjian; Peng, Zhongbi; Chen, Yun; Zhang, Lan; Liang, Lidan; Wang, Yi; Zhou, Hao (Frontiers in Pediatrics, 2025)
BackgroundChildren with autism often exhibit atypical eating behaviors, which may significantly impact their nutritional status and overall well-being. However, research on the dietary habits of Chinese children with autism remains limited.ObjectiveThis study primarily assesses the applicability of Brief Autism Mealtime Behavior Inventory (BAMBI) for Chinese children with autism, while further exploring the unique dietary behavior characteristics within this population.MethodsIn total, 103 children with autism aged 3–6 years and 331 typically developing preschoolers were recruited. All participants’ parents completed the Brief Autism Mealtime Behavior Inventory (BAMBI) and the Six-item Gastrointestinal Severity Index (6-GSI). The reliability and validity of the Chinese version of the BAMBI were analyzed, and differences in dietary behavior were tested between cases and controls.ResultsThe item reliability (Cronbach's alpha) was 0.849 for total BAMBI. Pearson correlation analyses of the full BAMBI scale scores and subscales revealed significant correlations (r values ranging from 0.580 to 0.912, P < 0.01). The confirmatory factor analysis result shows that BAMBI 18 items have an acceptable fit to the data (GFI = 0.901, CFI = 0.819, ILI = 0.821, RMSEA = 0.074). Although the value of average variance extra (AVE) of the main scale is slightly below 0.5, the composite reliability (CR) is both above 0.7. The ASD group scored significantly higher than the typically developing group in terms of the BAMBI total score and subscales. The top problematic dietary behaviors reported by parents were inflexible about mealtime routines (79.61%), unwilling to try new foods (75.73%) and not accepts or prefers a variety of foods (71.84%). The positive association between BAMBI total scores and 6-GSI scores was observed.ConclusionBAMBI is a validated tool for assessing dietary behaviors in autistic children in China. Compared with their typically developing peers, ASD children presented more dietary behavior problems. This study emphasizes early attention to dietary behavior problems in children with autism.